Արդի հայերենի տնտեսագիտական փոխառյալ տերմինների գործառական բնութագիրը - Ղարսլյան, Ա.
Предметом исследования данной статьи являются заимствованные экономические термины современного армянского языка, большая часть которых представляет собой интернациональные слова. Согласно этимологическому анализу заимствование терминов происходило из тех языков, на которых развивалась экономическая мысль и первые представления об экономике, а носители этих языков сыграли определенную роль в становлении и развитии экономики как отдельной дисциплины. В качестве социальной науки экономика тесно сотрудничает с общественными и естественными науками, в результате чего формируются междисциплинарные и общие терминосистемы. Во избежание скопления иностранных слов в языке, со временем делаются попытки создания армянских эквивалентов, из которых отбираются те варианты, которые являются благозвучными для общества и полностью передают все значения семантического поля того или иного понятия. The given article aims to study the borrowed economic terms of Modern Armenian, most of which are words of international significance. According to the etymological analysis, the borrowed terms were taken from those languages in which the first economic thoughts and ideas were expressed, the speakers of which had a significant role in the formation and establishment of economics as a separate discipline. Economics, as a social science, is in close cooperation with social and natural sciences, as a consequence of which interdisciplinary and general terminology systems are formed. Avoiding the accumulation of foreign words in the language, in the course of time attempts are being made to create equivalent versions in the Armenian language, among which are chosen the versions that are pleasant to the ear of the society and fully express the semantic field of the concept.
Keywords: Տերմինաբանություն